Bibliography: Terrorism and Justice Systems, Courts, and Detention - Tinnes, Judith (Perspectives on terrorism, 2024)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on the multifaceted relationship between terrorism and incarceration. It covers multiple aspects, including the radicalisation of prisoners, the risk assessment of detainees, and human rights issues relating to imprisoned terrorists and terrorism suspects. It focuses on recent publications (up to November 2024) and should not be considered as being exhaustive. The literature has been retrieved by manually browsing more than two hundred core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.